Synergistic effects of local herbal extracts on wound healing with hibiscus rosa-sinensis and centella asiatica - Ali, Aida Azlina (Faculty of Pharmacy, 2025)
Wound healing is a vital biological process that ensures tissue repair and restores skin integrity following injury. Although the skin naturally heals through complex mechanisms involving inflammation, proliferation, and remodelling, these processes can be delayed or impaired by factors such as infection, chronic disease, or aging. To address these challenges, researchers are actively exploring innovative ways to enhance healing, with particular interest in natural products with medicinal properties. In this context, a recent study by our research team, comprising researchers from UiTM, UPM and UKM, has yielded promising results through the synergistic use of two traditional medicinal plants, Hibiscus rosa-sinensis and Centella asiatica (HRSCA).